Harrison's principles of internal medicine - Longo, Dan L. (Dan Louis); Harrison, Tinsley Randolph (McGraw-Hill, 2012)
"With the 18th edition, Harrison's Principles of Internal Medicine retains its standing as a definitive clinical reference and remains an outstanding foundation for any physician or physician-in-training. In many regards, Harrison's remains synonymous not just with internal medicine but with medicine in general. The editors of the 18th edition have skillfully balanced tradition with the desire and need for innovation. The result is a book that remains as fundamental to current medical practice as the first edition was in 1949."